Klasterisasi Tukang Gigi di Jakarta dengan Algoritma K-Means berdasarkan Daerah Asal - Zulkarnain, Iskandar; Fauziyah, Fauziyah (Universitas Wahid Hasyim, 2024)
Tukang gigi registered with the Indonesian tukang gigi Union (STGI) DPW DKI Jakarta organization are 625 members. STGI is an organization that has been incorporated by the Ministry of Law and Human Rights number AHU-000083. AH.01.08.Year 2020. In the distribution of tukang gigi in Jakarta consisting of various regions of origin, the researcher conducted clustering research to find out the distribution of the origin of Tukang Gigi in the Jakarta area. The scope of the research data area is: North Jakarta, West Jakarta, East Jakarta, South Jakarta and Central Jakarta. The results of the clustering of the K-Means Algorithm using the RapidMiner application are as follows: Cluster 0 (C0) : 1 Member, Cluster 1 (C1) : 16 Members, Cluster 2 (C2) : 1 Member. The results included in C0 are the Regency/City of origin of the most tukang gigi, namely: Pamekasan. The results included in C1 are the most diverse Regencies/Cities of the origin of tukang gigi, consisting of 16 Regencies/Cities, including the 3rd most Tukang Gigi' origin areas, namely: Jakarta. While those included in C2 are the 2nd most tukang gigi from origin, namely: Jember.